Matrine induces senescence of human glioblastoma cells through suppression of the IGF1/PI3K/AKT/p27 signaling pathway. (5th August 2018) - Zhou, Wenjing; Wang, Jiwei; Qi, Qichao; Feng, Zichao; Huang, Bin; Chen, Anjing; Zhang, Di; Li, Wenjie; Zhang, Qing; Bjerkvig, Rolf; Li, Xingang; Wang, Jian
Abstract: Background: Matrine, a traditional Chinese medicine, has recently been shown to have antitumor properties in diverse cancer cells. Here, we explored the effect of matrine on human glioblastoma multiforme (GBM) cells. Methods: Glioblastoma multiforme cell lines were treated with matrine to assess proliferation and viability using EdU and CCK8 assays. SA‐β‐gal assays were used to evaluate cellular senescence, and a cytokine array and ELISA assay were used to screen for secreted cytokines altered in GBM cells after matrine treatment. Immunohistochemistry and Western blot analysis were performed to evaluate protein levels in matrine‐treated cell lines and in samples obtained from orthotopic xenografts. Specific activators of AKT and IGF1 were used to identify the pathways mediating the effect. Results: Matrine potently inhibited growth of GBM cell lines in vitro. Based on in situ assays, growth arrest induced by matrine was primarily achieved through induction of cellular senescence. Matrine treatment led to decreased expression of proteins involved in promoting cell growth, IGF1, PI3K, and pAKT. Exposure of cells to a small molecule activating AKT (SC79) and recombinant IGF1 led to a reduced number of senescent SA‐β‐gal‐positive cells in the presence of matrine. Finally, matrine inhibited growth of orthotopic xenografts established from luciferase‐stable‐U251 or luciferase‐stable‐P3 cells and prolonged overall survival in mice. Conclusions: These results indicated that matrine arrested cell growth through inhibition of IGF1/PI3K/AKT signaling. Matrine warrants further investigation as a potential therapy in the treatment of patients with GBM. Abstract : In this study, we investigated the effects of the Chinese traditional medicine matrine on GBM cells. We report that matrine inhibits proliferation of GBM cells by inducing senescence in cells in vitro by suppressing PI3K/AKT/p27 signaling. Matrine‐induced senescence was further enhanced through downregulation of IGF1. Finally, we demonstrate that matrine suppresses growth of orthotopic xenografts and prolongs overall survival of mice. Thus, our study provides new insights into the molecular mechanisms underlying matrine‐mediated inhibition of GBM cell proliferation and demonstrates the therapeutic relevance of modulating senescence in malignant brain tumors.